INDEPENDENT CURRUCULUM DEVELOPMENT IN EDUCATIONAL UNITS AND ITS APPLICATION IN 21st CENTURY LEARNING - Wirawan, Zose; Arwien, Rizki Trisnawaty; Safira, Ifa; Sumartini, Rini; Bachri, Salsabilah Syaeful (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
Curriculum development needs to be carried out by educational units in anticipation of the increasingly rapid pace of development of Science and Technology. The aim of this research is to understand the process of curriculum development in Indonesia, especially the independent curriculum which is implemented in educational units. As well as knowing the application or implementation of the independent curriculum in 21st century learning. The research method used is literature study, namely data collection techniques carried out by systematically searching scientific literature, whether in the form of journals, articles, books or other sources. The research results show that curriculum development needs to be carried out to produce graduates who are in line with the demands of the future. The implementation of the independent curriculum includes 3 activities, namely intracurricular, co-curricular and extracurricular. Education units can choose the options implemented in the independent curriculum, including independent learning, independent change and independent sharing. The implementation of the independent curriculum must also be in accordance with current 21st century learning which has the characteristics of the 4C abilities that students must have, namely Critical Thinking, Communication, Collaboration and Creativity.